Two-dimensional nanosheets produced by liquid exfoliation of layered materials. - Coleman, J; Lotya, M; O'Neill, A; Bergin, S; King, P; Khan, U; Young, K; Gaucher, A; De, S; Smith, R; Shvets, I; Arora, S; et al. (2011)
If they could be easily exfoliated, layered materials would become a diverse source of two-dimensional crystals whose properties would be useful in applications ranging from electronics to energy storage. We show that layered compounds such as MoS(2), WS(2), MoSe(2), MoTe(2), TaSe(2), NbSe(2), NiTe(2), BN, and Bi(2)Te(3) can be efficiently dispersed in common solvents and can be deposited as individual flakes or formed into films. Electron microscopy strongly suggests that the material is exfoliated into individual layers. By blending this material with suspensions of other nanomaterials or polymer solutions, we can prepare hybrid dispersions or composites, which can be cast into films. We show that WS(2) and MoS(2) effectively reinforce polymers, whereas WS(2)/carbon nanotube hybrid films have high conductivity, leading to promising thermoelectric properties.